Is Change in Hemoglobin Level a Predictive Biomarker of Tyrosine Kinase Efficacy in Metastatic Renal Cell Carcinoma? A Turkish Oncology Group Study. (21st April 2017) - Bilir, Cemil; Yıldız, İbrahim and Bilici, Ahmet and Ucar, Mahmut and Berk, Veli and Yıldız, Yaşar and Yazıcı, Ozan and İmamoğlu, Gökşen İnanç and Karadurmuş, Nuri and Pilancı, Kezban Nur and Arpacı, Erkan and Tanrıverdi, Özgür and Karcı, Ebru and Temiz, Süleyman and Nayır, Erdinc and Oktay, Esin and Dal, Pınar and Petekkaya, İbrahim and; m, Ceyhun and; mre, Hakan
ABSTRACT: Background : There are insufficient predictive markers for renal cell carcinoma (RCC). Methods : A total of 308 metastatic RCC patients were analyzed retrospectively. Results : The increased hemoglobin (Hb) group had significantly higher progression-free survival and overall survival (OS) compared with the decreased Hb group at 11.5 versus 6.35 months ( p < .001) and 21.0 versus 11.36 months ( p < .001) respectively. The 1- and 3-year OS rates were higher in the Hb increased group, i.e., 84% versus 64% and 52% versus 35% respectively. Conclusions : The present study showed that increased Hb levels after tyrosine kinase inhibitor therapy could be a predictive marker of RCC.